Pengaruh Penggunaan Media Flash Card terhadap Kemampuan Pemahaman Kosa Kata Bahasa Inggris: Siswa Kelas 2 SD IT Wahdah Islamiyah 01 Antang - Sri Syahriani; Patta, Rahmawati; Putri Atjo, Syamsuryani Eka (PT Ininnawa Paramacitra Edukasi, 2024)
This research is based on the problem of students' low ability to understand English vocabulary. The aims of this research are: 1) to find out the description of the use of flash card media at SD IT Wahdah Islamiyah 01 Antang, 2) to find out the description of students' ability to understand English vocabulary at SD IT Wahdah Islamiyah 01 Antang, and 3) to find out whether there are Whether or not the use of flash card media has an influence on the ability to understand English vocabulary of students at SD IT Wahdah Islamiyah 01 Antang. This research is included in experimental research with a quantitative approach. The design used in this research is a quasi-experimental type with a nonequivalent control group design. Data collection techniques use tests and observation. The data analysis techniques used are descriptive and inferential analysis. The results of the descriptive analysis show that the use of flash card media is very effective. The results of inferential analysis using the independent sample t-test showed that t-count > t-table so that the Ha hypothesis was accepted and Ho was rejected. Based on the research results, it can be concluded that: 1) The use of flash card media was carried out very effectively. 2) The ability to understand language vocabulary after using flash card learning media has increased. 3) There is an influence of the use of flash card media on students' ability to understand English vocabulary in class II of SD IT Wahdah Islamiyah 01 Antang.